Characterizations of juvenile stages of some semaeostome Scyphozoa (Cnidaria), with recognition of a new family (Phacellophoridae - Straehler-Pohl, I.; Widmer, C. L.; Morandini, A. C. (Zootaxa, 2011)
Phacellophora camtschatica has long been assigned to the semaeostome scyphozoan family Ulmaridae. Early stages (scyphistomae, strobilae, ephyrae, postephyrae, and young medusae) of the species were compared with those of several other semaeostomes currently assigned to Ulmaridae, Pelagiidae, and Cyaneidae. Juveniles of P. camtschatica did not strictly conform with characters of those of any of these families, and appeared intermediate between Cyaneidae and Ulmaridae. A new family, Phacellophoridae, is proposed to accommodate P. camtschatica.